2004
DOI: 10.1002/ijc.20608
|View full text |Cite
|
Sign up to set email alerts
|

Novel markers for poor prognosis in head and neck cancer

Abstract: Head and neck cancer (HNSCC) is one of the most distressing human cancers, causing pain and affecting the basic survival functions of breathing and swallowing. Mortality rates have not changed despite recent advances in radiotherapy and surgical treatment. We have compared the expression of over 13,000 unique genes in 7 cases of matched HNSCC and normal oral mucosa. Of the 1,260 genes that showed statistically significant differences in expression between normal and tumor tissue at the mRNA level, the three to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 25 publications
4
113
0
5
Order By: Relevance
“…INK4a (45)(46)(47)(48)(49)(50)(51)(52) or p21 WAF1/CIP1 (17,(21)(22)(23)(24)51). Nevertheless, this is a controversial issue, with other researchers reporting a relationship between these proteins and survival (9,(18)(19)(20)53).…”
Section: Discussionmentioning
confidence: 99%
“…INK4a (45)(46)(47)(48)(49)(50)(51)(52) or p21 WAF1/CIP1 (17,(21)(22)(23)(24)51). Nevertheless, this is a controversial issue, with other researchers reporting a relationship between these proteins and survival (9,(18)(19)(20)53).…”
Section: Discussionmentioning
confidence: 99%
“…SPARC is known to interact with other matrix molecules such as collagen I, vitronectin and thrombospondin and with integrin-linked kinase (Rosenblatt et al, 1997;Barker et al, 2005a) and SPARCdeficient cells were recently found to exhibit defective DNA nuclear excision repair (Kato et al, 2005). Elevated SPARC expression has been found in many human malignancies including prostate, breast, colon, hepatocellular, head and neck, and non-small-cell lung carcinomas (Le Bail et al, 1999;Thomas et al, 2000;Lussier et al, 2001;Koukourakis et al, 2003;Jones et al, 2004;Chin et al, 2005). In prostate carcinoma, SPARC expression in cancer cells is associated with bone metastasis (Thomas et al, 2000).…”
Section: Functional Characterization Of St7 Cs-f Hooi Et Almentioning
confidence: 99%
“…Subsequently, caveolin-1 activation leads to invagination of the cell membrane to form transcytotic vesicles called caveolae, which transport albumin (and nab-P) across the endothelial cell to the interstitial space [13]. The albumin-binding matricellular protein SPARC (secreted protein, acidic and rich in cysteine), which is often over-expressed in many tumors, may also contribute to the higher intratumoral concentration of nab-P. SPARC has been associated with a poor prognosis in multiple tumors, including squamous cell cancer of the head and neck, Non-small cell lung carcinoma and breast cancer [14][15][16]. The amount of SPARC over-expression and the role SPARC may have in the increased intratumoral uptake or sequestration of nab-P is an area of active investigation in various malignancies.…”
Section: Chemistrymentioning
confidence: 99%